Consumer preferences to pay a price premium for quality attributes in Pakistani grown mangoes - Asif Yaseen; Mubashir Mehdi; Simon Somogyi; Burhan Ahmad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
Consumer preferences in food products are complex and multidimensional in nature, whose measurement requires the designing of succinctly validated scales. This study investigates how urban consumers perceive quality of locally grown mangoes varieties in Pakistan and how much extra price they are willing to pay for these quality attributes. Data was collected through a survey employed at supermarkets in five major cities of Pakistan, and responded 304 randomly selected consumers. Partial least square structural equation modelling was employed in the analysis. The results showed a dimensional structure representing the mango quality perceptions, profiled through extrinsic and intrinsic attributes, and consumers are willing to pay significantly different price premiums for quality attributes in mangoes. The findings of the study will be useful for the policy makers and mango value chain actors because quality in fresh fruits such as mangoes play a key role in determining the final market value of the produce and acceptance by the consumers to pay price premiums. This study contributes to advancing the knowledge on fruit consumption behavior in a developing country where existing research on assessing the willingness-to-pay with actual behavior is scant.
Keywords: 330; perceived quality; consumer preferences; willingness-to-pay; partial least square analysis; structural equation method; mango; Pakistan